HARTA PENAMA BUKAN HARTA PEMBERIAN DAN WASIAT - Muhammad, Abd Kadir (Jurnal Syariah, 2019)
The article adresses the contradiction of the courts' decision on harta penama (nominated property). The contradiction arises from the differences between the legal interpretation of the property and its meaning based on the requirement of the Syariah. The intricacy becomes more complicated when the terms harta wasiat (testated property) and harta pusaka (in testa ted property) are wrongly used as far as the Syariah Law is concerned. The article suggests that harta penama is not harta pemberian (gift), or harta wasiat.